26th Annual Conference of the International Group for Lean Construction 2018
DOI: 10.24928/2018/0391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Why Quantity Surveyors Conflict With Collaborative Project Delivery System

Abstract: Ahmed S.N, Pasquire C., and Manu, E. (2018). "Evaluating why quantity surveyors conflict with collaborative project delivery system" In: Proc. 26 th Annual Conference of the International. Group for Lean Construction (IGLC), González, V.A. (ed.), Chennai, India, pp. 1272-1282 ABSTRACTThe recurring poor performance and lack of collaborative culture in the UK construction industry has been a topic of debate for many years now. This has triggered an industry wide demand for performance improvement and innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Nguyen and Waikar (2018) stress the importance of a collaborative culture for a successful implementation of Lean but do not elaborate further on the subject. Ahmed et al (2018) discuss the lack of collaborative culture in UK construction. By looking at the performance of quantity surveyors, they concluded that factors such as persistent practices, inefficient procurement approaches, and narrowed views on collaboration hindered a better collaborative performance.…”
Section: Introductionmentioning
confidence: 98%
“…Nguyen and Waikar (2018) stress the importance of a collaborative culture for a successful implementation of Lean but do not elaborate further on the subject. Ahmed et al (2018) discuss the lack of collaborative culture in UK construction. By looking at the performance of quantity surveyors, they concluded that factors such as persistent practices, inefficient procurement approaches, and narrowed views on collaboration hindered a better collaborative performance.…”
Section: Introductionmentioning
confidence: 98%